Functional Abdominal Pain in Childhood: Background Studies and Recent Research Trends - Rona L Levy; Miranda AL van Tilburg (Pain Research and Management)
The present review summarizes many of the major research trends investigated in the past five years regarding pediatric functional abdominal pain, and also summarizes the primary related findings from the authors’ research program. Specific areas discussed based on work within the authors’ group include familial illness patterns, genetics, traits, and mechanisms or processes related to abdominal pain. Topics covered from research published in the past five years include prevalence and cost, longitudinal follow-up, overlap with other disorders, etiology and mechanisms behind functional abdominal pain and treatment studies. It is hoped that findings from this work in abdominal pain will be interpreted as a framework for understanding the processes by which other pain phenomena and, more broadly, reactions to any physical state, can be developed and maintained in children. The present article concludes with recommendations for clinical practice and research.